RANCANG BANGUN APLIKASI AUGMENTED REALITY KATALOG BARANG ELEKTRONIK BERBASIS ANDROID MENGGUNAKAN UNITY 3D - Agus Sugiharto (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2019)
E-Catalog (electronic catalog) is a list that contains information and is made electronically. E-Catalog is one of the most developed concepts in the world of information technology. This development brought many changes to the sector of business activity which had been carried out in the real world. The change was marked by the existence of a number of efforts from the business activity sector which was originally based in the real world (real), then developed it into the virtual world (virtual). One example of using augmented reality is advertising media. If we watch a football match often seen ads run on the screen at the edge of the field. Actually the advertisement did not happen or was actually displayed on the stadium, only television viewers saw it. This is because the television station is adding the image of the ad as a virtual object on the football broadcast it receives. Another example is making a film or news program on television such as weather news where the host appears to be on a map to show the weather forecast to be delivered. The term is a green screen or green screen, which is by using a large green background screen, we can replace the background with another display digitally. The military has for years been using augmented reality technology in the form of a cockpit display that displays information to pilots on the cockpit protective glass or the windshield of their flight helmets. Augmented Reality has been widely used in the world of entertainment, business, medical, design and engineering, robotics and telerobotics, manufacturing, education, etc. There are many more uses of AR technology in everyday life. Developers try various modifications to create tools that can combine the real world and cyberspace with benefits that can be felt more by its users.